2014
DOI: 10.1103/physreve.89.022122
|View full text |Cite
|
Sign up to set email alerts
|

Numerical studies on critical properties of the Kosterlitz-Thouless phase for the gauge glass model in two dimensions

Abstract: The critical exponents are estimated for the gauge glass model in two dimensions, in which only the Kosterlitz-Thouless (KT) phase appears in the low-temperature regime. The nonequilibrium relaxation method is applied to estimate the transition temperature and critical exponents: the static exponent η and the dynamical exponent z. Since the system exhibits criticality in the whole KT phase, we estimate the exponents on the boundary as well as inside the KT phase. The static exponent η depends on both the tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
(100 reference statements)
1
8
0
Order By: Relevance
“…On the other hand, since the flow from ρ 4 = 1 can end in the infrared onto any point of the line (18), also the disordered model should exhibit a BKT phase, and this is confirmed by numerical studies (see e.g. [24,25]). The phase diagram observed in these studies is similar to that of Fig.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…On the other hand, since the flow from ρ 4 = 1 can end in the infrared onto any point of the line (18), also the disordered model should exhibit a BKT phase, and this is confirmed by numerical studies (see e.g. [24,25]). The phase diagram observed in these studies is similar to that of Fig.…”
mentioning
confidence: 63%
“…1, with the ferromagnetic phase replaced by the BKT phase 3 . On the other hand, numerical studies still disagree on the values of critical exponents along the portion of the phase boundary going from the multicritical point M to the critical point of the pure model: a constant magnetic exponent η = 1/4 (the value at the BKT transition in the pure model) was deduced in [24], while a continuously varying η was found in [25].…”
mentioning
confidence: 98%
“…The effect of a finite amount of phase disorder has been studied in some detail: Extensive work on randomphase XY (RPXY) models [13][14][15][16][17][18][19][20][21][22][23][24] -without frustrationhas established 15,22 that the ground state has QLRO with power-law correlations at small disorder; this state continuously connects to the QLRO phase at finite T . Upon increasing the disorder strength a KT-like transition destroys the QLRO phase in favor of a disordered phase with exponentially decaying correlations.…”
Section: Frustrated Xy Models and Random-phase Disordermentioning
confidence: 99%
“…The critical disorder strength decreases with increasing temperature. While it was initially argued from perturbative considerations 13 that a re-entrant behavior might be observed where the dependence of critical disorder strength for the KT transition is non-monotonic with temperature and at zero temperature the critical disorder strength vanishes, non-perturbative treatments [15][16][17]19,21 and Monte-Carlo (MC) simulations [22][23][24] have shown that the RPXY model does not exhibit any re-entrant behavior and the QLRO phase survives upto a finite critical value of disorder strength even at T = 0.…”
Section: Frustrated Xy Models and Random-phase Disordermentioning
confidence: 99%
See 1 more Smart Citation